Membangun Budaya Siaga Bencana melalui Simulasi Gempa Bumi dan Tsunami di Lingkungan Madrasah Aliyah Negeri 2 Suak Timah - Raina Parmitalia Dinda; Rita Fazlina; Rezqi Malia; Alvisyahri Alvisyahri; Veranita Veranita; Astiah Amir; Fadli Idris; Dewi Purnama Sari; Fitry Hasdanita; Rahmat Djamaluddin; Rinaldy Rinaldy; Zulyaden Zulyaden; Fachruddin Fachruddin (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2026)
This community service activity aimed to build a disaster preparedness culture through earthquake and tsunami simulation activities at Madrasah Aliyah Negeri 2 Suak Timah, West Aceh Regency. The activity was motivated by the high risk of earthquake and tsunami disasters in the coastal area of West Aceh and the limited understanding of students regarding disaster mitigation and evacuation procedures. This program was carried out through collaboration between the Regional Disaster Management Agency (BPBD) of West Aceh Regency, lecturers from the Civil Engineering Department of Teuku Umar University, the Samatiga Community Health Center, and the school. The methods used included education, socialization, demonstrations, and direct simulations regarding self-rescue actions during earthquakes and tsunamis. The simulation was conducted at Suak Timah Football Field as the evacuation gathering point. The results showed an increase in students’ and school members’ knowledge and preparedness in facing disasters. Participants were able to understand evacuation routes, perform self-protection actions, and follow evacuation procedures in an orderly and rapid manner. Evaluation results indicated that disaster mitigation understanding reached 85%, self-rescue ability 88%, accuracy in following evacuation routes 90%, discipline during simulation 92%, and participant involvement reached 95%. This activity also encouraged the formation of a disaster awareness culture and the emergence of active student roles as preparedness pioneers within the school environment. Therefore, disaster simulation proved to be an effective educational medium in improving the capacity and preparedness of school communities toward earthquake and tsunami risks.